New 5-Alkenyl Resorcinols from Lithraea molleoides (Vell). Eng. - Catalano, Alejandra Vanina (2020)
Lithraea molleoides (Anacardiaceae) is a tree that grows in South America including Southern Brazil, Southern, and Eastern Bolivia, Southern Paraguay, Northern, and Central Argentina. Infusions, decoctions, or tinctures from its aerial parts (leaves, buds, and young stems) are employed in ethnomedicine mainly against respiratory, and digestive inflammations and illnesses. Antibacterial, antiviral, antioxidant, antiinflammatory, and antinociceptive activities, among others, have been reported for L. molleoides. Many of its biological activities have been associated with the reported presence of 5-alkenyl resorcinols. Alkyl/alkenyl catechols and alkyl/alkenyl resorcinols are very common in members of the Anacardiaceae family and several activities have been attributed to them. This work describes the isolation and the structural elucidation of three new 5-alkenyl resorcinols isolated from Lithraea molleoides reported in nature for the first time.